The Moderating Role of Drinking Water Habit on the Effect of High- Purine Dietary Intake on Uric Acid Levels in Adults and the Elderly - Rahmawati, Anita; Lestari, Amelia Anggi Dwi; Fata, Ulfa Husnul (Journal of Ners and Midwifery, 2025)
Serum uric acid levels are affected by dietary patterns and lifestyle factors. High-purine food consumption is a primary contributor to hyperuricemia, while hydration status may moderate this effect. This study aimed to examine the moderating role of drinking water habits on the relationship between high-purine dietary intake and serum uric acid levels among adults and the elderly. A cross-sectional design with purposive sampling was conducted, involving 87 respondents from Elderly Integrated Health Post (Posyandu Lansia). Data on purine-rich food intake and water-drinking habits were collected via structured questionnaires, and serum uric acid levels were measured using a point-of-care testing (POCT) device (Easy Touch GCU 3-in-1) with compatible test strips. Multiple logistic regression analysis assessed the interaction between purine intake and drinking water habits. Results revealed a significant association between high-purine dietary intake and elevated serum uric acid levels (p = 0.022). Participants who reported high-purine dietary habits along with insufficient water consumption demonstrated the highest prevalence of hyperuricemia (71.4%), whereas those with similar dietary patterns but adequate hydration showed a substantially lower prevalence (20.0%). A significant interaction effect (p = 0.040) indicated that sufficient water intake moderated the impact of a high-purine diet on uric acid levels. Adequate hydration thus plays a critical moderating role in reducing the adverse effects of a high-purine diet. Promoting sufficient water intake may serve as a simple and effective behavioral strategy to prevent hyperuricemia, particularly among individuals with high purine consumption.